2016
DOI: 10.1098/rsta.2015.0167
|View full text |Cite
|
Sign up to set email alerts
|

Length scales and pinning of interfaces

Abstract: One contribution of 11 to a theme issue 'Trends and challenges in the mechanics of complex materials' . The pinning of interfaces and free discontinuities by defects and heterogeneities plays an important role in a variety of phenomena, including grain growth, martensitic phase transitions, ferroelectricity, dislocations and fracture. We explore the role of length scale on the pinning of interfaces and show that the width of the interface relative to the length scale of the heterogeneity can have a profound ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 21 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…In this case, previous study has suggested that the pinning of phase boundary by the heterogeneity can be strong [29].…”
Section: Effects From Heterogeneity Elasticity and Initial Nucleimentioning
confidence: 77%
See 1 more Smart Citation
“…In this case, previous study has suggested that the pinning of phase boundary by the heterogeneity can be strong [29].…”
Section: Effects From Heterogeneity Elasticity and Initial Nucleimentioning
confidence: 77%
“…There are non-photoactive heterogeneities in the semi-crystalline polymer such as the chain extender, crosslinks, residual solvents or initiators, and other precipitates. These heterogeneities can play important roles in the evolution of phase transition through pinning the phase boundaries with possible stick-slip behaviors [29,30]. We include the effect of this heterogeneity by a quenched spatial noise described in Section II.D, and now examine it in more detail.…”
Section: Effects From Heterogeneity Elasticity and Initial Nucleimentioning
confidence: 99%
“…There are diverse thoughts about hysteresis in a large literature, 11 some of which are in fact inconsistent with the observation of rateindependent hysteresis. Ideas also include the pinning of interfaces by defects [61] and spin flips in an Ising model mediated by disorder [56]. There is also a deep mathematical literature on the modeling of hysteresis, which is not so much concerned with its origins, but rather with the accurate simulation of hysteresis loops [44].…”
Section: Hysteresismentioning
confidence: 99%
“…The analysis of contact stress around these area is important in understanding the onset and propagation of those failures: it will provide guidelines for the design of contact components so that the damage can be limited [11,12,[15][16][17][18][19][20][21]. Based on experimental observations, the sliding behavior between two elastic bodies in contact can be described by three regimes on a map of tangential and normal loads: full-stick, partial-slip and gross-sliding regimes [22][23][24].…”
Section: Introductionmentioning
confidence: 99%